Crop breeding to break nexus between bee decline/food production? - Hamblin, J.; Barbetti, M.; Stefanova, Katia; Blakeway, F.; Clements, J.; Cowling, W.; Guo, Y.; Nichols, P. (2018)
© 2018 Elsevier B.V. Yield of 70% of crops are reported to benefit from animal pollination, primarily by bees. There are major concerns that honey bee (Apis mellifera) decline will reduce food production. Current research focuses on bee health and its impact on crop production. Pollinators are considered essential for high yields of thirteen crops including melons. Here we show it is possible to select genotypes of several crops, including melons, where yield is independent of pollinators. This approach, for managing the pollination/production nexus, has not been widely considered. We contrast our results and methodology with reports used to determine a crop's need for bee pollination. Uptake of bee independent varieties will depend on whether the species is herbaceous or perennial. Our results suggest the potential impact of bee decline has been significantly over-estimated.